Effect of A rehabilitated motor physical program for Illiotatibial band syndrome in a long distance runner - darwish ahmed, Hossam (International Journal of Psychosocial Rehabilitation, 2019)
Background: Illotibial band syndrome is one of the most common knee injuries, which appear in the form of pain in the lateral front of the knee in runners caused by inflammation of the distant or lateral part of the illotibial ligament. The illotibial band is the most common injury of the lateral side of the knee in runners, with an incidence estimated to be between 5% and 14%. In Order to facilitate the evidence-based management of ITBS in runners, more It needs to be learned about the etiology, diagnosis, and treatment of this injury. The illotibial band syndrome results in great illness and thus disability. (144: 27) Methods: The sample of the study included one experimental group consisting of (10) of the participants of the rehabilitation centers of sports and natural medicine and rehabilitation of the patients with Iliotibial band syndrome syndrome (20-30), The researcher is the experimental approach due to its relevance to the subject of the research Objective: This article provides a systematic review of the literature on the etiology, diagnosis, and treatment of ITBS in runners. Systematic reviews, clinical trials, or observational studies involving adult runners (20 > years) that focused on the etiology, diagnosis, and/or treatment of ITBS were included. Results: The proposed therapeutic program works on the decline and disappearance of pain, restoration of motor range, restoration of patellar bone to normal, and restoration of elastic and muscle strength. Cooling using ice (ice bag) affects the affected part of the pain relief and control of inflammation and improves the psychological state. Recommendation: need rapid treatment of injury after the beginning of the sense of pain and after careful diagnosis to rapid treatment, rehabilitation, and avoid the occurrence of complications. And take all preventive measures (over-training) rationing of loads, stress on exercises, flexibility, lengthening, and strength of the thigh muscles